2022
DOI: 10.1093/sleep/zsac199
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin suppression does not automatically alter sleepiness, vigilance, sensory processing, or sleep

Abstract: Pre-sleep exposure to short-wavelength light suppresses melatonin and decreases sleepiness with activating effects extending to sleep. This has mainly been attributed to melanopic effects, but mechanistic insights are missing. Thus, we investigated whether two light conditions only differing in the melanopic effects (123 vs. 59 lux melanopic EDI) differentially affect sleep besides melatonin. Additionally, we studied whether the light differentially modulates sensory processing during wakefulness and sleep. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 75 publications
2
14
2
Order By: Relevance
“…The lack of significant differences in sleep timing and sleep quality indices (sleep diaries or actigraphy) between patients grouped by DLMO onset, DLMO offset, and non-calculable DLMO, at T0 or T1, may be in relation to the complexity of the condition of the patients, the limited number of DLMO available, and the fact that the timing of melatonin production is obviously not the sole determinant of sleep timing/ quality (Lavie, 1997;De Rui et al, 2015;Blume et al, 2022), especially in a complex and unusual situation such as hospitalization. The lack of a relationship between melatonin profiles and subjective or objective sleep-wake variables may also suggest that confounders such as medication or illness per se may play a relevant role on melatonin profile shape and DLMO/DLMOff computability/timing in clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of significant differences in sleep timing and sleep quality indices (sleep diaries or actigraphy) between patients grouped by DLMO onset, DLMO offset, and non-calculable DLMO, at T0 or T1, may be in relation to the complexity of the condition of the patients, the limited number of DLMO available, and the fact that the timing of melatonin production is obviously not the sole determinant of sleep timing/ quality (Lavie, 1997;De Rui et al, 2015;Blume et al, 2022), especially in a complex and unusual situation such as hospitalization. The lack of a relationship between melatonin profiles and subjective or objective sleep-wake variables may also suggest that confounders such as medication or illness per se may play a relevant role on melatonin profile shape and DLMO/DLMOff computability/timing in clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…While one study reported increased sleepiness the other study found no effect (Xu 2018). Interestingly, a recent study by the Cajochen group (Blume et al 2022) found that although melatonin was suppressed by nighttime exposure to SWL, this did not translate to altered levels of vigilance or sleepiness. The authors suggest that an interaction between melanopsin and cone-rod signals needs to be considered.…”
Section: Physiological Effects Of Swl Exposurementioning
confidence: 99%
“…Light exposure can also have acute NIF impacts on alertness, sleep, and cognition, all with a sensitivity shifted toward shorter wavelength light (~460 nm) [ 5 , 67 , 68 , 69 , 70 , 71 ]. Though, it should be noted that the acute NIF effects of light may not be due to a direct result of melatonin suppression through melanopsin-ipRGC suppression [ 72 ]. Light impact on alertness has been measured with subjective and objective measures with both kinds showing that light exposure increases alertness.…”
Section: Light: Circadian and Acute Impactsmentioning
confidence: 99%